Assimilation exceeds respiration sensitivity to drought: A FLUXNET synthesis - CHRISTOPHER R. SCHWALM; CHRISTOPHER A. WILLIAMS; KEVIN SCHAEFER; ALMUT ARNETH; DAMIEN BONAL; NINA BUCHMANN; JIQUAN CHEN; BEVERLY E. LAW; ANDERS LINDROTH; SEBASTIAAN LUYSSAERT; MARKUS REICHSTEIN; ANDREW D. RICHARDSON (Global Change Biology, 2010)
The intensification of the hydrological cycle, with an observed and modeled increase in drought incidence and severity, underscores the need to quantify drought effects on carbon cycling and the terrestrial sink. FLUXNET, a global network of eddy covariance towers, provides dense data streams of meteorological data, and through flux partitioning and gap filling algorithms, estimates of net ecosystem productivity ( F NEP ), gross ecosystem productivity ( P ), and ecosystem respiration ( R ). We analyzed the functional relationship of these three carbon fluxes relative to evaporative fraction (EF), an index of drought and site water status, using monthly data records from 238 micrometeorological tower sites distributed globally across 11 biomes. The analysis was based on relative anomalies of both EF and carbon fluxes and focused on drought episodes by biome and climatic season. Globally P was ≈50% more sensitive to a drought event than R . Network‐wide drought‐induced decreases in carbon flux averaged −16.6 and −9.3 g C m −2 month −1 for P and R , i.e., drought events induced a net decline in the terrestrial sink. However, in evergreen forests and wetlands drought was coincident with an increase in P or R during parts of the growing season. The most robust relationships between carbon flux and EF occurred during climatic spring for F NEP and in climatic summer for P and R . Upscaling flux sensitivities to a global map showed that spatial patterns for all three carbon fluxes were linked to the distribution of croplands. Agricultural areas exhibited the highest sensitivity whereas the tropical region had minimal sensitivity to drought. Combining gridded flux sensitivities with their uncertainties and the spatial grid of FLUXNET revealed that a more robust quantification of carbon flux response to drought requires additional towers in all biomes of Africa and Asia as well as in the cropland, shrubland, savannah, and wetland biomes globally.

Separation of net ecosystem exchange into assimilation and respiration using a light response curve approach: critical issues and global evaluation - GITTA LASSLOP; MARKUS REICHSTEIN; DARIO PAPALE; ANDREW D. RICHARDSON; ALMUT ARNETH; ALAN BARR; PAUL STOY; GEORG WOHLFAHRT (Global Change Biology, 2010)
The measured net ecosystem exchange (NEE) of CO 2 between the ecosystem and the atmosphere reflects the balance between gross CO 2 assimilation [gross primary production (GPP)] and ecosystem respiration (R eco ). For understanding the mechanistic responses of ecosystem processes to environmental change it is important to separate these two flux components. Two approaches are conventionally used: (1) respiration measurements made at night are extrapolated to the daytime or (2) light–response curves are fit to daytime NEE measurements and respiration is estimated from the intercept of the ordinate, which avoids the use of potentially problematic nighttime data. We demonstrate that this approach is subject to biases if the effect of vapor pressure deficit (VPD) modifying the light response is not included. We introduce an algorithm for NEE partitioning that uses a hyperbolic light response curve fit to daytime NEE, modified to account for the temperature sensitivity of respiration and the VPD limitation of photosynthesis. Including the VPD dependency strongly improved the model's ability to reproduce the asymmetric diurnal cycle during periods with high VPD, and enhances the reliability of R eco estimates given that the reduction of GPP by VPD may be otherwise incorrectly attributed to higher R eco . Results from this improved algorithm are compared against estimates based on the conventional nighttime approach. The comparison demonstrates that the uncertainty arising from systematic errors dominates the overall uncertainty of annual sums (median absolute deviation of GPP: 47 g C m −2 yr −1 ), while errors arising from the random error (median absolute deviation: ∼2 g C m −2 yr −1 ) are negligible. Despite site‐specific differences between the methods, overall patterns remain robust, adding confidence to statistical studies based on the FLUXNET database. In particular, we show that the strong correlation between GPP and R eco is not spurious but holds true when quasi‐independent, i.e. daytime and nighttime based estimates are compared.